Antioxidant sordariol dimers from Sordaria macrospora and the absolute configuration determinations of their two simultaneous linear 1, 2-diols. Issue 25 (22nd June 2016) - Li, Tianxiao; Wang, Xiaobing; Luo, Jun; Yang, Minghua; Kong, Lingyi
Graphical abstract: Highlights: Four novel sordariol dimers were isolated from Sordaria macrospora . They exhibited potent antioxidant activities. Double-derivatization NMR methods were used for their acyclic 1, 2-diols. Abstract: One new sordariol derivative (1 ), four novel sordariol dimers (2 –5 ), together with four known compounds (6 –9 ) were isolated from solid cultures of an endophytic fungus Sordaria macrospora that was obtained from the bark of Ilex cornuta . Compounds2 and3 were first identified as 5, 12′-carbon bond linked sordariol dimers possessing new carbon skeletons, while4 and5 were elucidated as novel sordariol dimers with ether bond linkages. The challenging absolute configurations of their two simultaneous acyclic 1, 2-diols were unambiguously determined by the double-derivatization NMR method. In antioxidant assays, compounds2 –4 exhibited potent ABTS (2, 2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) radical cation scavenging activities with EC50 values of 12.2–14.5 μM, 2-folds more potent than the positive control trolox (EC50  = 26.7 μM).